RELIGIUSITY OF STANDARD TRADERS COMMUNITIES IN THE COVID-19: Researech On Street Vendors at Ciparay Maket Bandung - HIKMAT (Universal Institute of Professional Management, 2021)
This study aims to get an overview of the socio-economic reality of Ciparay street vendors during the Covid-19 pandemic. And to get an idea of the religious activities of the Ciparay Bandung street vendors during the Covid-19 period. The method used is the quality method with the technique used is observation, subsequent literature documentation interviews, data obtained in the field are analyzed to deepen the focus of this research. The results of the study show, First that the implementation of PSBB and PPKM to suppress the mobility of people's movements, was able to significantly reduce the speed of the spread of the Covid-19 pandemic, but economically it was not profitable, especially felt directly by street vendors in the Ciparay area, Bandung district, so they felt the difficulty. income to cover daily life. Second. The religious activities of the PKL Ciparay Bandung community during the Covid-19 period after the implementation of the health protocol (PSBB/PPKM). Their level of religiosity is getting higher while surrendering but still praying to Allah SWT, so that the Covid-19 virus outbreak will end soon and the economic situation will improve soon. Religious activities in free time selling are carried out by reading the Qur'an and while continuing to pray, asking for forgiveness from Allah SWT, in addition, carrying out the routine of Ibadan praying five times directly to the Great Mosque of Ciparay Bandung which has just been renovated. Of course the atmosphere in the mosque is now more conducive, safer and more comfortable to get closer to Allah SWT.